2011
DOI: 10.1007/s00276-011-0872-0
|View full text |Cite
|
Sign up to set email alerts
|

An anatomical study of the transverse part of the infraspinatus muscle that is closely related with the supraspinatus muscle

Abstract: Basic science study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 28 publications
6
53
0
Order By: Relevance
“…The larger, lower oblique part of infraspinatus sits below the transverse part of the muscle, which lies just below and in parallel, with supraspinatus. 25 It is also suggested that the transverse part of infraspinatus shares an innervation with supraspinatus, different to the oblique part of infraspinatus. 25 The structure of infraspinatus may be central to the difficulty in isolating it from supraspinatus.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The larger, lower oblique part of infraspinatus sits below the transverse part of the muscle, which lies just below and in parallel, with supraspinatus. 25 It is also suggested that the transverse part of infraspinatus shares an innervation with supraspinatus, different to the oblique part of infraspinatus. 25 The structure of infraspinatus may be central to the difficulty in isolating it from supraspinatus.…”
Section: Discussionmentioning
confidence: 98%
“…25 It is also suggested that the transverse part of infraspinatus shares an innervation with supraspinatus, different to the oblique part of infraspinatus. 25 The structure of infraspinatus may be central to the difficulty in isolating it from supraspinatus. Not only does its insertion extend more anteriorly than previously thought, but also the structure of the muscle, with the transverse part possibly being more closely related to supraspinatus morphologically, may mean that it may not act as one, with different parts of the muscle being activated in a different manner.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In support of this, a recent study has proposed a novel anatomical and functional perspective of the insertion anatomy of the cuff into the greater tuberosity, and related studies have been performed to support these findings. 5,6) For instance, Kato et al 7) described the infraspinatus 31 tendon in terms of the direction of fibrosis: the oblique component and the transverse component. Using their method to divide the infraspinatus muscle into four compartments, Matsuki et al 8) found that the superior compartment was associated with around half the tears of the anterior infraspinatus whereas the inferior compartment was associated with half the tears of the posterior infraspinatus.…”
Section: Introductionmentioning
confidence: 99%